2022
DOI: 10.21873/invivo.12790
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Cisplatin/Carboplatin, 5-Fluorouracil Plus Cetuximab (EXTREME) for Advanced-stage Salivary Gland Cancer

Abstract: Background/Aim: Surgery remains the standard treatment for salivary gland carcinoma (SGC). Our study investigated the association between epidermal growth factor receptor (EGFR) status in recurrent/metastatic SGC and the effectiveness of treatment with cisplatin/carboplatin and 5fluorouracil plus cetuximab (EXTREME). Patients and Methods: We retrospectively collected 19 SGCs from patients treated with the EXTREME regimen. After analyzing EGFR expression and gene copy number gain, we evaluated the correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, anti-EGFR therapies, besides our study, could not show efficacy in patients with SGC. Two studies using anti-EGFR monotherapy (cetuximab [21] and gefitinib [22]) showed no clinical responses, and one study using cetuximab combined with cisplatin and fluorouracil showed poor ORR (11.1%) [27]. Thus, it is surprising that our study demonstrated the promising efficacy of Cmab-PTX in patients with recurrent SGC, with an ORR of 71.4%, despite all cases being high-grade histological types.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, anti-EGFR therapies, besides our study, could not show efficacy in patients with SGC. Two studies using anti-EGFR monotherapy (cetuximab [21] and gefitinib [22]) showed no clinical responses, and one study using cetuximab combined with cisplatin and fluorouracil showed poor ORR (11.1%) [27]. Thus, it is surprising that our study demonstrated the promising efficacy of Cmab-PTX in patients with recurrent SGC, with an ORR of 71.4%, despite all cases being high-grade histological types.…”
Section: Discussionmentioning
confidence: 71%
“…All the previous studies regarding anti-HER-2 therapies subjected to HER-2 positive SGC patients [19,[23][24][25][26]28]. However, previous studies using anti-EGFR therapies with poor clinical outcomes included patients with negative EGFR [21,22,27]. In our study, all measurable patients with SGC were positive for EGFR in immunostaining and showed preferable results with anti-EGFR therapy.…”
Section: Characteristics Of Patients and Treatment Outcomesmentioning
confidence: 63%
See 2 more Smart Citations
“…Chemotherapy is not consensual (10,12,13,15). Nakano and colaborators (2022) retrospectively identified 19 patients through a study who were treated with the EXTREME chemotherapy regimen (cisplatin/carboplatin, 5-fluorouracil plus cetuximab) for advanced-stage salivary gland cancer, where the best responses observed in this study were only partial responses observed in 2 cases (mucoepidermoid carcinoma and one of LEC), but even with this fact all cases had treatment discontinuation due to adverse effects (16).…”
Section: Discussionmentioning
confidence: 99%